Dimensionally stable anodes for the oxygen evolution reaction: Ruthenium dioxide on a nickel metal substrate. (12th September 2022) - Jovic, Vedran; Sullivan, Matthew; Keßler, Philipp; Gupta, Prasanth; Fiedler, Holger; Spencer, Sarah; Moser, Simon; Marshall, Aaron T.; Kennedy, John V.
Abstract: Dimensionally stable anodes (DSA) for the oxygen evolution reaction (OER) gradually passivate under operating conditions due to the formation of insulating TiO2 at the interface of the Ti-metal substrate and the catalytically active metal oxide layer (typically a mixture of ruthenium and iridium oxides). The incorporation of a catalytically active, yet stable, interfacial buffer layer or substrate is a potential means of promoting the overall performance. Here, we prepared DSA-like RuO2 on Ni films by the thermal decomposition method and contrast their OER activity with an analogous RuO2 on Ti-metal film. The fabrication process resulted in the presence of NiO and Ni oxides/(oxy)hydroxides at the surface of the rutile RuO2 layer. Along with RuO2, the former species were active in the water splitting reaction under the testing conditions. Ni–RuO2 films showed lower OER overpotentials relative to Ti–RuO2 suggesting a synergistic effect between Ni- and Ru-oxides and the Ni layer between Ti and RuO2 to improve overall performance. Further studies should optimize the NiO–RuO2 loading levels, understand the NiO–RuO2 synergy toward catalytic performance and determine the stability under accelerated testing conditions. Highlights: Nickel screened as a substrate or interfacial buffer layer in DSAs. Using an intuitive fabrication method, Ni forms a mixed metal oxide with RuO2 . Catalyst layer of NiO–RuO2 synergistically improves the OER activity. Direction offered for studies focused on optimizing DSA composition and stability.